Translating Human Nature and Merit in Matteo Ricci's Tianzhu shiyi (The True Meaning of the Lord of Heaven) - Hu, Cui'e (The catholic historical review, 2025)
Studies on the influence of Jesuit Sinology have tended to focus on the emergence of chinoiserie and Orientalism, and less often on the philological background of literary and philosophical exchange. This article places Matteo Ricci's work of translation in Tianzhu shiyi within a broader context to show how he extended and enriched the Confucian theories and concepts about human nature and moral cultivation, and how the Western theories of human nature and merit underwent subtle transformation in the process. If viewed from the perspective of cultural fundamentalism, it seems that Ricci misinterpreted and subverted the orthodox Confucian doctrines of the inherent goodness of human nature and self-cultivation. From the perspective of cultural communication that seeks common ground while reserving valid differences, however, Ricci's misreading has instead extended and enriched these Confucian doctrines.